Identification of Novel Locus RsCr6 Related to Clubroot Resistance in Radish (Raphanus sativus L.) - Gan, Caixia; Yan, Chenghuan; Pang, Wenxing; Cui, Lei; Fu, Pengyu; Yu, Xiaoqing; Qiu, Zhengming; Zhu, Meiyu; Piao, Zhongyun; Deng, Xiaohui (Frontiers in Plant Science, 2022)
Clubroot is a devastating disease that causes substantial yield loss worldwide. However, the inheritance and molecular mechanisms of clubroot resistance during pathogen infection in radish remain largely unclear. In this study, we investigated the inheritance of clubroot resistance in the F2 population derived from crossing clubroot-resistant (CR) and clubroot-susceptible inbred lines “GLX” and “XNQ,” respectively. Genetic analysis revealed that a single dominant gene controlled the clubroot resistance of “GLX” with a Mendelian ratio of resistance and susceptibility of nearly 3:1. Bulked segregant analysis combined with whole-genome resequencing (BSA-seq) was performed to detect the target region of RsCr6 on chromosome Rs8. Linkage analysis revealed that the RsCr6 locus was located between two markers, HB321 and HB331, with an interval of approximately 92 kb. Based on the outcomes of transcriptome analysis, in the RsCr6 locus, the R120263140 and R120263070 genes with a possible relation to clubroot resistance were considered candidate genes. In addition, three core breeding materials containing the two reported quantitative trait loci (QTLs) and our novel locus RsCr6 targeting clubroot resistance were obtained using marker-assisted selection (MAS) technology. This study reveals a novel locus responsible for clubroot resistance in radishes. Further analysis of new genes may reveal the molecular mechanisms underlying the clubroot resistance of plants and provide a theoretical basis for radish resistance breeding.